Protective and detoxifying effects conferred by selenium against mycotoxins and livestock viruses: A review - Fang, Manxin; Hu, Wei; Liu, Ben (Frontiers in Veterinary Science, 2022)
Abstract Animal feed can easily be infected with molds during production and storage processes ,this can lead to the production of secondary metabolites such as mycotoxins which eventually threaten human and animal health. Furthermore, livestock production is also not free from viral infections. Under these conditions, the essential trace element Selenium (Se) can confer various biological benefits to human and animals, especially due to its anticancer, antiviral and antioxidant properties as well as its ability to regulate immune responses. This paper reviews the latest literature on the antagonistic effects of Se on mycotoxin toxicity and viral infections in animals.We outlined the systemic toxicity of mycotoxins as well as the primary mechanisms of mycotoxins-induced toxicity in the present analysis. Additionally, we pay close attention to how mycotoxins and viral infections in livestock interact. The use of Se supplementation against mycotoxin-induced toxicity and cattle viral infection was the topic of our final discussion. The coronavirus disease 2019 (COVID-19) pandemic, which is currently causing a health catastrophe, has altered our perspective on health concerns to one that is more holistic and increasingly embraces the One Health Concept, which acknowledges the interdependence of humans, animals, and the environment. In light of this, we have made an effort to present a thorough and wide-ranging background on the protective functions of selenium in successfully reducing mycotoxin toxicity and livestock viral infection. It concluded that mycotoxins could be systemically harmful and pose a severe risk to human and animal health. On the other hand, animal mycotoxins and viral illnesses have a close connection. Last but not least, these findings show that the interaction between Se status and host response to mycotoxins and cattle virus infection is crucial.